Understanding Preschool Children’s Reported Knowledge of Food, Nutrition, and Health - Tsao, Ling-Ling; Ramsay, Samantha (International Journal of Child Health and Nutrition, 2016)
Early childhood is recognized as a key time period in the prevention of overweight and obesity. The knowledge young children gain about food and its health benefits for the body may impact their dietary choices and preferences later in life. Therefore, this study aimed to assess the nutrition knowledge of young children. A total of 26 children participated in a one-on-one interview with the researcher. Among five common food items, most children were able to label the food items, but fewer children were able to successfully place them into food groups (e.g., MyPlate). Children also were able to describe the food, but they did not accurately report what benefit the food was to the body. The results suggest the need to reinforce child-centered nutrition education appropriate for young children’s cognitive development